PEMBANGUNAN IMPRASTRKTUR JALAN DIDESA KABUPATEN SINTANG - Syamsudin, Martinus (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
Abstract: The main problem examined in this research is the development of road infrastructure in villages in Sintang Regency. Therefore, the objectives of this study are to determine, describe, and analyze the development of road infrastructure in villages in Sintang Regency. This research method uses descriptive research. The subjects were the Village Head, Hamlet Head, and the community. The research techniques used for data collection were observation, interviews, and documentation studies, with data analysis using qualitative descriptive analysis methods. The results of this study indicate that the majority of residents support the improvement of village road infrastructure in planning village road development to facilitate daily activities and economic progress. Community participation in road infrastructure development has been effective in decision-making, implementation, and utilization. The conclusion of this study is that village road development planning has been carried out through the construction of new roads and repairs to facilitate daily activities and economic progress. Community participation in road infrastructure development has involved all elements of the community. Coordination has been established.